Digital Socio-Technical Innovation and Indigenous Knowledge - Poline, Bala; Narayanan, Kulathuramaiyer; Chong Eng, Tan (IntechOpen, 2022)
Scientific research involving remote rural communities is often plagued by a lack of understanding of what constitutes indigenous knowledge. That is, indigenous perspectives, models of representation, and their ways of knowing. Through a long-standing community-university partnership in working with remote and rural communities in the Borneo Malaysian states of Sarawak and Sarawak and the Orang Asli communities in Peninsular Malaysia, we address this concern in presenting directions for shaping digital socio-technical innovation. We highlight the need to adopt a balanced indigenous worldview based on two case studies from past interactions with these indigenous communities to highlight how indigenous knowledge can now become contextualized within contemporary problem-solving scenarios.